(untitled) (Biological Sciences - PJSIR, 1998)
This paper presents the results of some investigations on the melting of selenium ruby glasses, particularly on the effect or AI20j and I3p) on ruby colour. / glass of base composition (wt. %) Si02 65.0, Nap l5.5,Kp 5.3, ZnO l2.0, H201 1.0. CdS 0.6, Sc 0.6 has been chosen for these studies. To this glass Alp) and Bpj arc systematically substituted for Na20 in small amounts from 0.5 to 3.0%. Effects of these substitutions on melting, refining, colour, striking temperature etc. have been recorded. Transmittance of some representative samples has been determined. Glasses containing AI20] 1.5 and 2’.0% and having Bp) 2.0 to 3.0% alongwith 1.0% Al20l have been found suitable for the development of red signal glasses. Pilot Plant meltings also gave satisfactory results.